An exploration of the institutionalisation of public relations at executive level in the top 100 companies listed on the Johannesburg Stock Exchange (JSE) - Elizabeth Ferreira; Rene Engelbrecht (Communicare)
This article discusses the institutionalisation of public relations at executive level in large organisations, based on research applied to a purposive sample of the top 100 companies listed on the Johannesburg Stock Exchange (JSE) in South Africa. Based on an examination of recent literature on public relations as a strategic management function, the study aimed to determine the extent to which senior public relations practitioners in the selected companies are involved in strategy formulation and decision-making at executive level. Current and recent literature provided a conceptual framework based on the premise that organisations have much to gain by involving senior practitioners in top-level decision-making and strategy formulation. The following theories informed the primary research, which took the form of qualitative semi-structured interviews with the participating practitioners: excellence theory, the dominant coalition, the relational approach, the reflective paradigm and roles theory, with the main focus on the strategic role of public relations. Apart from indicating the extent to which public relations is practiced as a top-level management function in the selected companies, the study also sought to identify barriers that prevent the participating practitioners from providing strategic input at an executive level, and to offer recommendations to overcome these barriers.